'A double-edged sword. This is powerful but it could be used destructively': Perspectives of early career researchers on learning analytics - Jenna Mittelmeier; Rebecca L. Edwards; Sarah K. Davis; Quan Nguyen; Victoria L. Murphy; Leonie Brummer; Bart Rienties (EARLI, 2018)
Learning analytics has been increasingly outlined as a powerful tool for measuring, analysing, and predicting learning experiences and behaviours. The rising use of learning analytics means that many educational researchers now require new ranges of technical analytical skills to contribute to an increasingly data-heavy field. However, it has been argued that educational data scientists are a 'scarce breed' (Buckingham Shum et al., 2013) and that more resources are needed to support the next generation of early career education researchers. At the same time, little is known about how early career researchers feel towards learning analytics and whether it is important to their current and future research practices. Using a thematic analysis of a participatory learning analytics workshop discussions with 25 early career researchers, we outline in this article their ambitions, challenges and anxieties towards learning analytics. In doing so, we have provided a roadmap for how the learning analytics field might progress and practical implications for supporting early career researchers' development.